Sex and Gender Differences in Myocarditis and Dilated Cardiomyopathy - Fairweather, DeLisa (2013)
Heart failure due to nonischemic dilated cardiomyopathy (DCM) contributes significantly to the global burden of cardiovascular disease. Myocarditis is in turn a major cause of acute dilated cardiomyopathy in both men and women. However, recent clinical and experimental evidence suggests that the pathogenesis and prognosis of DCM differ between the sexes. This seminar provides a contemporary perspective on the immune mediators of myocarditis, including interdependent elements of the innate and adaptive immune response. The heart's acute response to injury is influenced by sex hormones that appear to determine the subsequent risk of chronic DCM. Preliminary data suggest additional genetic variations may account for some of the differences in epidemiology, left ventricular recovery and survival between men and women. We highlight the gaps in our knowledge regarding the management of women with acute DCM and discuss emerging therapies, including bromocriptine for the treatment of peripartum cardiomyopathy.